The Second International Conference on Modern Slavic Literary Theories and Comparative Poetics (ENTHYMEMA, 2016)
This is a report of the Second International Conference on Modern Slavic Literary Theories and Comparative Poetics jointly held in Guangzhou from June 25th to 26th, 2016 by the Research Council for Foreign Literary Theories and Comparative Poetics in China, the Research Center for Literary Theories of Chinese Academy of Social Sciences，the Chinese National Association of Comparative Literature and Literary Theories,the  Bachtin Research Center in China, the Center for Foreign Literature and Culture of Guangdong University of Foreign Studies and the Faculty of European Languages and Culture of Guangdong University of Foreign Studies